2021
DOI: 10.1016/j.molcel.2021.03.034
|View full text |Cite
|
Sign up to set email alerts
|

The dystonia gene THAP1 controls DNA double-strand break repair choice

Abstract: The Shieldin complex, consisting of SHLD1, SHLD2, SHLD3 and REV7, shields DNA double strand breaks (DSBs) from nucleolytic resection. The end-protecting activity of Shieldin promotes productive non-homologous end joining (NHEJ) in G1 but can threaten genome integrity during S-phase by blocking homologous recombination (HR). Curiously, the penultimate Shieldin component, SHLD1 is one of the least abundant mammalian proteins. Here, we report that the transcription factors THAP1, YY1 and HCF1 bind directly to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 104 publications
2
16
0
Order By: Relevance
“…On the contrary, inactivating Shieldin complex by Shld1 KO or Shld2 KO lifts the block on both DNA end resection and RNF168-mediated PALB2 loading. Therefore, Shld1 KO or Shld2 KO rescues embryonic lethality of Brca1 Δ11/Δ11 mice and no obvious abnormalities are reported for Brca1 Δ11/Δ11 ;Shld1 −/− or Brca1 Δ11/Δ11 ;Shld2 −/− mice, suggesting that HR is likely restored (Ling et al, 2020;Shinoda et al, 2021). In line with these observations, Rnf168 KO rescues both embryonic lethality and HR of Brca1 Δ2/Δ2 mice, which produce BRCA1ΔRING protein that efficiently interacts with PALB2 (Zong et al, 2019).…”
Section: Rescue Of Hr Repair Defects Caused By Brca1 Deficiencysupporting
confidence: 63%
“…On the contrary, inactivating Shieldin complex by Shld1 KO or Shld2 KO lifts the block on both DNA end resection and RNF168-mediated PALB2 loading. Therefore, Shld1 KO or Shld2 KO rescues embryonic lethality of Brca1 Δ11/Δ11 mice and no obvious abnormalities are reported for Brca1 Δ11/Δ11 ;Shld1 −/− or Brca1 Δ11/Δ11 ;Shld2 −/− mice, suggesting that HR is likely restored (Ling et al, 2020;Shinoda et al, 2021). In line with these observations, Rnf168 KO rescues both embryonic lethality and HR of Brca1 Δ2/Δ2 mice, which produce BRCA1ΔRING protein that efficiently interacts with PALB2 (Zong et al, 2019).…”
Section: Rescue Of Hr Repair Defects Caused By Brca1 Deficiencysupporting
confidence: 63%
“…Epistasis between 53BP1-RIF1 and the SHLD complex is remarkable in multiple NHEJ reactions, including CSR, the fusion of telomeres lacking TRF2, and the repair of DSBs in BRCA1-deficient cells treated with PARP inhibitors [23][24][25] . In AID-inducible B cell lines, loss of any of the SHLD complex components similarly impairs CSR that is associated with enhanced DSB end resection and the accumulation of chromosomal breaks at immunoglobulin switching sites [26][27][28][29][30][31][32][33][34] . In mice, loss of REV7 or SHLD2 does not impact lymphocyte development while severely compromising CSR 27,30 .…”
mentioning
confidence: 99%
“…Intriguingly, several studies have demonstrated that THAP1 frequently co‐occupies its target genes with the transcriptional co‐regulators YY1 and HCFC1 (Mazars et al, 2010; Michaud et al, 2013; Shinoda et al, 2021; Yellajoshyula et al, 2017), which are recruited to the promoters by THAP1 (Hollstein et al, 2017; Yellajoshyula et al, 2017). Nevertheless, the interest in YY1 in the context of dystonia is quite a new issue and there is certainly much more to be explained.…”
Section: Dystoniamentioning
confidence: 99%